Is the Central Valley of Costa Rica a genetic isolate? - Morera, Bernal (2004)
In the last decade, the Costa Rican Central Valley population (CRCV), has received considerable scientific attention, attributed in part to a particularly interesting population structure. Two different and contradictory explanations have emerged: (1) An European-Amerindian-African admixed population, with some regional genetic heterocigosity and moderate degrees of consanguinity, similar to other Latin-American populations. (2) A genetic isolate, with a recent founder effect of European origin, genetically homogeneous, with a high intermarriage rate, and with a high degree of consanguinity. Extensive civil and religious documentation, since the settlement of the current population, allows wide genealogy and isonymy studies useful in the analysis of both hypotheses. This paper reviews temporal and spatial aspects of endogamy and consanguinity in the CRCV as a key to understand population history. The average inbreeding coefficients (a) between 1860 and 1969 show a general decrease within time. The consanguinity in the CRCV population is not homogeneous, and it is related to a variable geographic pattern. Results indicate that the endogamy frequencies are high but in general it was not correlated with a values. The general tendency shows a consanguinity decrease in time, and from rural to urban communities, repeating the tendencies observed in other countries with the same degree of development, and follows the general Western World tendency. Few human areas or communities in the world can be considered true genetic isolates. As shown, during last century, the CRCV population has had consanguinity values that definitively do not match those of true genetic isolates. A clear knowledge of the Costa Rican population genetic structure is needed to explain the origin of genetic diseases and its implications to the health system